“The Experiences are Beyond our Expectations”: Changing the Culture of Artificial Intelligence and Social and Emotional Learning in Educational Institutions − A Qualitative Evaluation Among Representatives of the SETCOM Project Partners (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
In the evolving field of education, the intersection of artificial intelligence (AI) and social and emotional learning (SEL) is increasingly relevant. This article presents a qualitative evaluation among twelve representatives from eight SETCOM project partners to learn about their views, experiences and expectations regarding the project’s content and organization. The findings indicate that despite initial apprehensions about AI, there was enthusiasm for its potential intersection with SEL. Participants appreciated collaborative opportunities and sought practical applications for project insights, aiming to enhance existing programs and stimulate new ideas. Challenges included managing tasks amidst AI’s rapid evolution and the initial separation of the AI and SEL domains. The lack of AI regulations was a concern. Participants advocated for a proactive approach by educators in assessing AI applications, emphasizing ethical considerations in their use.